2016
DOI: 10.1249/mss.0000000000000862
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Capacity of the World’s Highest Ranked Female Cross-country Skiers

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
128
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(147 citation statements)
references
References 32 publications
15
128
3
1
Order By: Relevance
“…This is due to the polynomial relationship between speed and submaximal metabolic rate, which also results in GE to be speed-dependent (i.e., non-linear) (see Figures 2-4). Therefore, none of the more conventional methods for estimating the anaerobic capacity (i.e., the linear MAOD methods or both GE methods) can be recommended for DP, which has also been indicated in previous publications (Sandbakk et al, 2016;Andersson et al, 2017) -but not systematically analyzed. Therefore, when evaluating the anaerobic capacity in DP, the non-linear relationships for speed vs. metabolic rate and the nonlinear speed-dependency of GE suggests the use of alternative methods, such as the second-degree polynomial method (i.e., 8-Y POL ) described in the current study, or, alternatively, the method described by Beneke et al (2002).…”
Section: Different Effect Of Computational Methods In Dp and Ds Sub-tementioning
confidence: 99%
“…This is due to the polynomial relationship between speed and submaximal metabolic rate, which also results in GE to be speed-dependent (i.e., non-linear) (see Figures 2-4). Therefore, none of the more conventional methods for estimating the anaerobic capacity (i.e., the linear MAOD methods or both GE methods) can be recommended for DP, which has also been indicated in previous publications (Sandbakk et al, 2016;Andersson et al, 2017) -but not systematically analyzed. Therefore, when evaluating the anaerobic capacity in DP, the non-linear relationships for speed vs. metabolic rate and the nonlinear speed-dependency of GE suggests the use of alternative methods, such as the second-degree polynomial method (i.e., 8-Y POL ) described in the current study, or, alternatively, the method described by Beneke et al (2002).…”
Section: Different Effect Of Computational Methods In Dp and Ds Sub-tementioning
confidence: 99%
“…In a recent review, it was summarized that most retrospective studies on well-trained athletes report on PYR TID, although some world-class athletes performed POL TID during certain phases of the season (Stöggl and Sperlich, 2015). Sandbakk et al (2016), Tønnessen et al (2014), and Guellich et al (2009) reported a general focus on HVLIT TID in the preparation period, which became more polarized in the competition period of world/national class cross-country skiers, biathletes, and young world-class rowers.…”
Section: Introductionmentioning
confidence: 99%
“…In endurance sports, these include the duration and intensity of individual training sessions, the frequency of training sessions, and the organizational pattern of these stimulus variables over time. Recent descriptive studies of some of the world_s best endurance athletes have shown that successful athletes in cycling (14,25,35), running (1,2), and cross-country skiing (21,22,33) perform a high volume of low-intensity training (LIT) (defined as work eliciting a stable blood lactate concentration [la j ] of less than approximately 2 mmolIL j1 ) in addition to much smaller but substantial proportions of both moderate-intensity training (MIT) (2-4 mmolIL j1 blood lactate) and high-intensity training (HIT) (training above maximum lactate steady-state intensity [94 mmolIL j1 blood lactate]) throughout the preparation period. The majority of descriptive studies present a ''pyramidal'' training intensity distribution (TID), with high volume of LIT, substantial MIT, and less HIT, whereas a few studies suggest athletes to adopt a ''polarized'' TID (reduced volume of MIT, somewhat higher HIT), which have been proposed to give superior endurance adaptations (27,29).…”
mentioning
confidence: 99%